Proceedings of the 2001 annual workshop of JIRCAS Mekong delta project (Can Tho, 2001)
The progress reports contained in the workshop are meant to faciliate discussion during the review period.
Keywords: Agriculture,Cropping systems,Nông nghiệp,Hệ thống canh tác; Economic aspects,Khía cạnh kinh tế